ҚАРАҚАЛПАҚ ЭПОСЛАРЫНЫҢ СЫРТ ЕЛЛЕРДЕ ҮЙРЕНИЛИЎИНДЕ ХАЛЫҚ АРАЛЫҚ КОНФЕРЕНЦИЯЛАРДЫҢ ТУТҚАН ОРНЫ - Алламбергенова, Г.К. (ILIM hám JÁMIYET, 2022)
The article provides a detailed analysis of the scientific statements of foreign scholars at the international conferences on the study of Karakalpak epics in Nukus in 1997-2005. Also, these scientific theoretical conferences draw convincing conclusions about the great practical importance of promoting Karakalpak epics abroad.